2013
DOI: 10.1007/978-3-642-39053-1_35
|View full text |Cite
|
Sign up to set email alerts
|

Realizability Models Separating Various Fan Theorems

Abstract: Abstract. We develop a realizability model in which the realizers are the reals not just Turing computable in a fixed real but rather the reals in a countable ideal of Turing degrees. This is then applied to prove several separation results involving variants of the Fan Theorem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…What has been proved [33] is that WWKL is strictly weaker than WKL over RCA 0 , a weak (classical) subsystem of second order arithmetic. That proof was then adapted to a constructive setting in [16], but applied to the classical contrapositives of WKL and WWKL, there called D-FAN and W-D-FAN, respectively. It is then shown that the Yu-Simpson argument that WWKL does not imply WKL translates to a proof that over IZF W-D-FAN does not imply D-FAN.…”
Section: Model 18mentioning
confidence: 99%
“…What has been proved [33] is that WWKL is strictly weaker than WKL over RCA 0 , a weak (classical) subsystem of second order arithmetic. That proof was then adapted to a constructive setting in [16], but applied to the classical contrapositives of WKL and WWKL, there called D-FAN and W-D-FAN, respectively. It is then shown that the Yu-Simpson argument that WWKL does not imply WKL translates to a proof that over IZF W-D-FAN does not imply D-FAN.…”
Section: Model 18mentioning
confidence: 99%